Shear forming of 304L stainless steel – microstructural aspects. (2017) - Guillot, M.; McCormack, T.; Tuffs, M.; Rosochowski, A.; Halliday, S.; Blackwell, P
Abstract: Shear forming is an incremental cold forming process. It transforms 2D plates into 3D structures commonly consisting of conical geometry. Roller(s) push the blank onto a cone-shaped mandrel, resulting in a decrease of the initial thickness. The shear forming process has diverse advantages, such as improved material utilisation, enhanced product characteristics, good surface finish, consistent geometric control and reduced production costs. Shear forming has potential applications in a wide range of conical geometries used within advanced aerospace structures, which are currently manufactured from bulk forgings with high associated machining costs. Research findings related to shear forming have been published over the past two decades, however, important remaining questions have still to be answered, with this paper addressing one such gap associated with the material deformation mechanism. Several studies have demonstrated the impact of key process variables on the final geometry and surface roughness, such as the feeds, roller nose radius and mandrel/roller offset. Although the material outputs are essential, as they link directly with the mechanical properties of the final components, the microstructure and texture of the material after shear forming have rarely been studied. Achieving a greater understanding in this area could reduce the reliance upon mechanical testing to validate the process and ease the exploitation route of the technology into advanced aerospace applications. Firstly, this paper presents the principle of shear forming and its related terminology. Then, a brief overview of the shear forming process including its history and origin is given. The areas of focus are a selection of the main variables encountered within this process which could impact the final properties. The generation of local stresses due to deviations from the sine law, the angle variations, and forces required during the forming operation are also considered. This is explored in the context of forming 304L stainless steel plates. This paper is written based upon experiments which observed a 52% thickness reduction using one roller. Scanning Electron Microscopy (SEM), Electron BackScatter Diffraction (EBSD) and hardness testing were utilised to characterise the shear formed material. The initial heterogeneous microstructure with relatively equiaxed grains evolved into a microstructure with elongated grains along with shear bands. A texture analysis revealed a simple shear mechanism of deformation, and theoretical and experimental shears were found to match. Identifying the mechanism of deformation was the first step to a better understanding of the effect imparted by the shear forming process on the material. Further studies will look at the impact of the key process variables on both the microstructure and texture as well as heat treatment optimisation.